Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s11096-012-9671-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of three drugs for the treatment of S. aureus infections in Nigeria

Abstract: Ciprofloxacin should be used as first-line-treatment of S aureus in Lagos as it will lead to significant cost savings in the treatment of S. aureus infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Colonization of wounds by Staphylococcus aureus and rapid proliferation within damaged tissues often lead to disseminated infections [13,14]. Staphylococcus aureus is notorious for its ability to become resistant to antibiotics [15,16]. Plasmids are extrachromosomal DNA molecules that have been shown to carry genes for antibiotics resistance, a single plasmid can carry genes for resistance to multiple antibiotics [17].…”
Section: Introductionmentioning
confidence: 99%
“…Colonization of wounds by Staphylococcus aureus and rapid proliferation within damaged tissues often lead to disseminated infections [13,14]. Staphylococcus aureus is notorious for its ability to become resistant to antibiotics [15,16]. Plasmids are extrachromosomal DNA molecules that have been shown to carry genes for antibiotics resistance, a single plasmid can carry genes for resistance to multiple antibiotics [17].…”
Section: Introductionmentioning
confidence: 99%
“…In resistant isolates, amikacin was dominantly more cost-effective when compared to meropenem and imipenem [6]. As per Canadian study conducted by Chow et al, showed clindamycin dominated other drugs such as cephalexin, cloxacillin, levofloxacin, and amoxicillin+clavulanate with the lowest CER in the treatment of DFT [12].…”
Section: Discussionmentioning
confidence: 90%
“…Antibiotic resistance is a major worldwide problem, and its implication on public health is becoming overwhelming [4][5][6]. Culture test helps to identify the causative organism and the effective drugs against these organisms can be determined by susceptibility tests.…”
Section: Introductionmentioning
confidence: 99%
“…1 They used drug susceptibility results from 463 clinical isolates and then performed a cost-effectiveness analysis * using a decision table as an analytical model. 1 They used drug susceptibility results from 463 clinical isolates and then performed a cost-effectiveness analysis * using a decision table as an analytical model.…”
Section: Ciprofloxacin Conquers Staph Infectionsmentioning
confidence: 99%